Diversity of Epithelial Stem Cell Types in Adult Lung - Feng Li; Jinxi He; Jun Wei; William C. Cho; Xiaoming Liu (Stem Cells International)
Lung is a complex organ lined with epithelial cells. In order to maintain its homeostasis and normal functions following injuries caused by varied extraneous and intraneous insults, such as inhaled environmental pollutants and overwhelming inflammatory responses, the respiratory epithelium normally undergoes regenerations by the proliferation and differentiation of region-specific epithelial stem/progenitor cells that resided in distinct niches along the airway tree. The importance of local epithelial stem cell niches in the specification of lung stem/progenitor cells has been recently identified. Studies using cell differentiating and lineage tracing assays, in vitro and/or ex vivo models, and genetically engineered mice have suggested that these local epithelial stem/progenitor cells within spatially distinct regions along the pulmonary tree contribute to the injury repair of epithelium adjacent to their respective niches. This paper reviews recent findings in the identification and isolation of region-specific epithelial stem/progenitor cells and local niches along the airway tree and the potential link of epithelial stem cells for the development of lung cancer.